The Need for an Interdisciplinary Network of Investigations on HHT - Pasculli, G.; Sallustio, G.; Sabba, C. (Current Pharmaceutical Design, 2006)
In the last years, the understanding of HHT has greatly progressed. The two genes for most on cromosomes 9 and 12 have been discovered and the existence of a third involved gene has been predicted. Recent progress in the field of genetics has allowed the identification of many gene mutation thus facilitating the characterisation of the at risk members of the same family. Complications from bleeding or shunting (pulmonary AVMs) may be sudden and life-threatening (hemothorax, haemoptysis, stroke and brain abscess). Catastrophic events are preventable by early diagnosis and treatment. Appropriate screening programmes are mandatory and multi-specialistic cooperation is needed. Special centers have been developed in the world, where physicians, who are specialised and trained in all aspects of HHT, are working to develop better therapeutic approaches for the disease and to locate new genes in view of the future potential of gene therapy for this condition.
Keywords: hereditary hemorrhagic telangiectasia